Sodium Butyrate in The Treatment of Irritable Bowel Syndrome KG - Grabowska, Karolina; Grabowska, Martyna; Wiśniewska, Aleksandra; Dąbek, Jakub; Kosucka, Wiktoria; Balik, Dominik; Lara, Joanna; Kwaśniewska, Anna; Kaszyńska, Karolina; Kubicka, Jagoda (Quality in Sport, 2025)
Purpose of the research: The purpose of this study is to present current knowledge on the use of sodium butyrate in the treatment of irritable bowel syndrome (IBS), with a particular focus on its effects on the microbiota and intestinal barrier. Material and Methods: The study is based on a review of the scientific literature, including clinical and experimental studies on the effects of sodium butyrate on the gastrointestinal tract. Results: Sodium butyrate strengthens the intestinal barrier, exhibits anti-inflammatory effects and influences the microbiota. Clinical studies confirm that its supplementation reduces abdominal pain, improves bowel rhythm and reduces bloating in IBS patients, resulting in a better quality of life. Conclusions: Sodium butyrate has the potential to be an effective support for IBS therapy, but further research is needed to determine its long-term safety and optimal dosage. In addition, changes in faecal levels of short-chain fatty acids (SCFAs) may act as a potential biomarker for IBS, but extra studies are needed to confirm their diagnostic value and define accurate reference levels.